Synthesis process, thermal and electrical behaviors of Ti3C2Tx MXene - Demirelli, K.; Celik, A.; Aksoy, Y.; Yegin, M.; Barim, E.; Hanay, O.; Hasar, H. (Wiley-V C H Verlag Gmbh, 2024)
Synthesis of two-dimensional (2D) titanium carbide (Ti3C2Tx), with the name of MXene, by etching Ti3AlC2 (MAX) for different times 20 (v/v) % hydrofluoric acid (HF) at 40 degrees C was carried out. The influences of time, temperature and source of MAX on the synthesis of MXene were researched. The MXenes produced were characterized by fourier-transform & imath;nfrared (FT-IR) spectroscopy technique, energy dispersive x-ray spectroscopy (EDX), scanning electron microscopy (SEM), x-ray diffraction (XRD) and thermogravimetry (TG) instruments. Above 390 degrees C, MXene layers were considerably oxidizing and forming anatase and rutile phases of TiO2 under air atmosphere. The resistance of MAX and MXene was 3.6 Omega and 116 Omega, respectively. However, the resistance of the residual part of MXene heated to 620 degrees C considerably increased to 17850 Omega. This behavior is another important piece of evidence showing that the MXene crystal structure has changed significantly and transformed into a new chemical structure containing anatase and rutil titanium oxide (TiO2). The dielectric loss (& varepsilon;'') and alternating conductivity (delta(ac)) of the MAX and MXenes were determined from their impedance measurements. The & varepsilon;'' and delta(ac) values of MXene were compared with those of MAX. Direct curent conductivities of MAX and MXene produced for 24 h were found to be 0.016 S/cm and 0.0023 S/cm, respectively.
Syntheseprozess, thermisches und elektrisches Verhalten von Ti3C2Tx MXene
Keywords: kinetic electrical properties; MXene; nanosheets; thermal stability